Optimization of hormone combinations for root growth and bud germination in Chinese fir (Cunninghamia lanceolata) clone leaf cuttings - Shubin Li (Nature Portfolio, 2017)
Abstract In order to ascertain the optimal hormone combination for Chinese fir (Cunninghamia lanceolata) leaf cuttings, an L16(4)4 orthogonal test of 6-benzylaminopurine (6-BA), 1-naphthaleneacetic acid (NAA), and indole-3-butyric acid (IBA) (0, 10, 30, or 50 mg · L−1 of each exogenous hormone) immersion for 5, 10, 15, or 20 min was conducted. Callus initiation rate and rooting promotion rate were mainly affected by treatment time, root length increase by 6-BA concentration, and bud germination rate and plantlet formation rate by NAA concentration. The expected optimal combination for callus initiation rate was 50 mg · L−1 6-BA + 0 mg · L−1 NAA + 30 mg · L−1 IBA + 10 min; for rooting promotion rate, it was 0–10 mg · L−1 6-BA + 10 mg · L−1 NAA + 30 mg · L−1 IBA + 20 min; for bud germination rate, it was 50 mg · L−1 6-BA + 0–10 mg · L−1 NAA + 0–30 mg · L−1 IBA + 20 min; and for seedling formation rate for No. 4, it was 10 mg · L−1 6-BA + 10 mg · L−1 NAA + 0 mg · L−1 IBA + 20 min. Light microscopy image analysis revealed that a cluster of primordial cells was produced 40 days after cutting, and mastoid cells developed into peninsula cells in calli that were cultured for 50 days.